Analisis Pengaruh Digital Marketing Terhadap Peningkatan Penjualan Hasil Industri Rumahan Desa Samataring Kec. Kelara Kab. Jeneponto - K, Suprianto.; Suryaningsih, Suryaningsih; Irsang, Irsang (CV. Eureka Murakabi Abadi, 2025)
The rapid development of information technology currently has an impact on society in supporting various business activities. Samataring Village, one of the areas in Kelara District, Jeneponto Regency, has high regional potential in improving community welfare through home businesses created by the community itself. The purpose of this study is to determine the extent to which digital marketing is effective in increasing sales in order to obtain maximum profit. The method used is Descriptive verification where researchers describe the state of digital marketing in increasing sales volume. Correlation analysis is the analysis used in this study, partial hypothesis testing to determine its influence. The conclusion of this study is that digital marketing has a positive and significant effect on sales, meaning that the benefits of digital marketing on sales are very much needed because it will increase or decrease sales.